The Chemical Constituents and Antibacterial Activity of Essential Oil of Peucedanum ruthenicum (M. Bieb.) Rochel (Umbelliferae) leaf. - SHR Alavi; N Yassa; MR Fazeli; F Fouladi; L Salimi; Y Ajani (Institue of Medicinal Plants, ACECR, 2007)
The essential oil of Peucedanum ruthenicum leaf obtained by hydro distillation and was analyzed by GC and GC/MS. Among the 17 identified constituents accounting for 100% of the total oil, the major component was Thymol (57.79%). Antimicrobial activity of the essential oil was investigated against various Gram-positive and Gram-negative bacteria. The essential oil of P. ruthenicum showed activity against Gram-positive and Gram negative bacteria.